Hubungan Menarche, Pola Menstruasi, Dan Status Gizi Dengan Dismenorea Primer Pada Remaja Putri Di SMP Negeri 1 Ciranjang Kabupaten Cianjur : The Relationship Between Menarche, Menstrual Patterns, and Nutritional Status with Primary Dysmenorrhoea in Adolescent Girls at SMP Negeri 1 Ciranjang, Cianjur Regency - Febriana, Retta (Dohara POAJ, 2024)
Introduction: Dysmenorrhea occurs in teenagers with a prevalence ranging from 43% to 93% where around 74-80% of teenagers experience mild dysmenorrhea while the incidence of endometriosis in teenagers who do not respond positively to treatment for menstrual pain endometriosis is found in 67% of cases.The general aim of this research is to find outrelationship between menarche, nutritional status and menstrual patterns with dysmenorrhoea in adolescent girls at SMP Negeri 1 Ciranjang Cianjur Regency in 2022. Methods: The research that will be carried out in this research is analytical descriptive research namely research that describes each variable and then looks for the relationship between one variable with another variable using a cross-sectional approach. Results: Research result the majority of respondents namely 34 (64,2%) have a bad lifestyle the majority of respondents do not experience stress, namely 35 people (66%); the majority of respondents namely 30 people (56,6%) have normal menstrual patterns. Most of the respondents namely 27 people (50,9%) did not experience dysmenorrhoea. Discussion: There is a relationship the relationship between lifestyle, stress levels and menstrual patterns with the incidence of dysmenorrhea in young women at SMP Negeri 1 Ciranjang Cianjur Regency in 2022. Expected young women cancontrolling primary dysmenorrhea factors that can be changed such as lifestyle, stress levels, nutritional status and exercise habits through increasing knowledge and implementing healthy lifestyle patterns.